Students' Perspectives on the Use of Quizizz in English Learning - Nelly Natalia; Abdul Rohman; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
This research discusses using Quizizz by English teachers in SMP Negeri 22 Samarinda learning activities. This research aims at students’ perspectives on the use of Quizizz in English learning. Five students participated in this study. This research method uses Qualitative with descriptive approach interviews was conducted. From the data described, the researcher found that students have a positive perspective toward the use of Quizizz during English learning. They are happy and motivated to learn English using this application. Besides, this application helps students to practice questions to improve their skills. Furthermore, Quizizz helps them in increasing their interest in learning. It concluded that using Quizizz helps students in English learning activities.